THE ANALYSIS OF FACTORS AFFECTING SUSTAINABILITY REPORT DISCLOSURE AMONG IDX-LISTED HEALTH COMPANIES FOR THE PERIOD OF 2021-2023 - Palwaguna, I Made Pahangga; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2025)
This research seeks to examine how profitability, leverage, corporate governance (measured by the percentage of independent commissioners), and firm size influence the disclosures in sustainability reports. The research used purposive sampling, focusing on 33 healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, resulting in 57 data observations for analysis. SPSS Statistics 27 software was employed for data analysis. The results indicate that profitability and leverage do not significantly affect sustainability report disclosures. In contrast, corporate governance, represented by the proportion of independent commissioners, has a significantly negative effect on these disclosures, whereas firm size shows a significantly positive impact.